Faʿāliyyat al-Muḥādathah al-Yawmiyyah li Tarqiyat Mahārat al-Kalām ladā Talāmīdh Madrasah Raudlatul Ulum al-Mutawassiṭah al-Islāmiyyah Labuhan Batu Sumatra al-Shamāliyyah - Eka Fitri Indah Sari; Ismail Baharuddin; Irsal Amin (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2025)
The background of this study is the low level of Arabic speaking proficiency among class IX students of MTs Raudlatul Ulum in Labuhan Batu North Sumatra, as a result of the lack of oral practice during education, poor vocabulary proficiency, fear of using Arabic, and low level of self-confidence. This study aims to determine the effectiveness of daily conversation application to improve students' speech skills. This study is based on a quantitative approach with a quasi-experimental design in one group, and the tool used in this study was a pre- and post-oral test to measure the extent to which students' speech skills improved. The research sample consisted of class IX students at the school. The results of the one-sample t-test and the N-Gain test showed that the application of the daily conversation method contributed to the improvement of the students' speech skills. The t-test revealed that there were statistically significant differences in favor of the post-test (t = 440.075, Sig. = 0.000), which indicates the effectiveness of everyday conversation in improving speech skills. N-Gain's analysis also showed an upgrade rate of 22.78%, which is within the average level, indicating that daily conversation proved a real and moderate improvement in the students' ability to speak.